The developing countries and the CR-ROM (Revista de Biblioteconomia de Brasília, 1990)
The use of on-line data bases in developing countries is discussed, as well as the access to data bases on CD-ROM disks. The two access methods are compared by the costs they generate and the functionality they may offer in this environment. Certain not readily perceived characteristics of the CD-ROM are exposed increasing the understanding of the potencial of this new technology when applied to information delivery systems. Several facts learned during the development of an information dissemination project for Latin America and the Caribbean using CD-ROMs in the Pan American Health Organization are presented. In addition, some initially unsuspected consequences of the application of CD-ROMs in developing countries are also discussed.